Specifics of Epidural Compression Syndrome Surgery in Patients with Spinal Malignancy - O. I. Kit; D. E. Zakondyrin; E. E. Rostorguev; S. V. Yundin (Креативная хирургия и онкология)
Background. Epidural spinal cord compression (ESCC) is the most common neurological complication in metastatic spinal tumours.Materials and methods. The study included 87 spinal malignancy patients operated within 01.01.2014–30.09.2021. All patients had a  type of palliative decompressive and stabilising surgery: standard posterior access (SPA, 55  patients), minimally invasive posterior access (MPA, 22 patients) or anterior access (AA, 10 patients).Results. The patient cohorts did not differ significantly by the duration of surgery, length of hospital stay, rates and types of postoperative complications. The AA cohort revealed a statistical difference by intraoperative blood loss. A Karnofsky performance status was statistically improved post- vs. pre-surgery (p < 0.05) at no significant change of Frankel neurological function status (p > 0.05). A Kaplan — Meier curve analysis showed no significant survival rate variation among the surgical techniques. Discussion. Our results suggest that posterior access interventions should be considered optimal. We report no statistical difference in the postoperative neurological and performance status dynamics between both cohorts, which encourages the MPA use in all patients with minimal epidural compression.Conclusion. Posterior access with cytoreductive tumour removal in anterior spinal cord compression is advantageous over anterior surgery. A posterior access surgery with minimal spinal canal decompression is recommended in all patients with grade 1 tumoural epidural compression.